Can Denture Wearing Increase the Nutritional Status in Pre-Elderly and Elderly Patients? - Liliana Budiman; Chaidar Masulili; Nina Ariani (Association of Support to Oral Health Research (APESB), 2022)
Objective: To investigate the relationships among tooth loss, denture wearing, nutrition intake, and nutritional status. Material and Methods: This observational cohort study was conducted on 26 patients (≥ 45 years old) at the Faculty of Dentistry, Universitas Indonesia. Tooth loss was classified according to the Eichner Index. The Semi-quantitative Food Frequency Questionnaire was used to measure nutritional intake (kcal). Mini Nutritional Assessment Short Form (MNA-SF) and Handgrip Strength (HGS) assessments were employed to measure the nutritional status at baseline (before denture insertion), 1, 2, 3, 6, 9, and 12 months after denture use. Results: Significant differences in nutritional intake (p<0.05) between the Eichner B and C groups were noted at 3, 6, 9, and 12 months after using dentures. Significant increases in nutritional intake were noted after wearing the dentures (p<0.05) when compared with the baseline values. The nutritional status was considered normal in 65.4% of the patients at 12 months and 38.5% at baseline. Furthermore, the nutritional status 1, 2, 3, 6, 9, and 12 months after wearing denture was significantly improved compared with the baseline values (p<0.05). Significant differences in HGS (p<0.05) were observed between the Eichner B and C groups at 6, 9, and 12 months after using the denture. However, no significant differences in HGS were noted before and after wearing the denture (p<0.05). Conclusion: Denture wearing can improve the nutritional intake and status of pre-elderly and elderly patients.